PEANOW Prevalence study of abuse and violence against older women: literature review (Israel) - Alves, José Ferreira (2009)
The present paper pretends to identify, describe and compare the prevalence studies of elder abuse and neglect developed in Israel. The research method used international databases and specific keywords to develop the research. Results show the dominance of communitarian 2 setting in elderly abuse and neglect studies and a comprehensive approach to specific populations (Arab-Israeli, Jewish). The results indicate lower levels of prevalence of abuse and neglect (2.5% and 0.5%) when local sample are considered, whereas when the national survey is taken into account, higher prevalence indices of abuse (18%) and even higher of neglect (26%) can be observed. Emotional / psychological abuses, followed by neglect, were the prevalent forms of abuse. All instruments employed were purposely designed for the different studies through research of international literature. In conclusion, several characteristics of the abused elders and perpetrators do encountered what has been found in other developed countries revealing that family is probably the primary setting where elderly abuse and neglect takes place.